2021
DOI: 10.1002/rra.3910
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of software accuracy to estimate the bed grain size distribution from digital images: A test performed along the Rhine River

Abstract: The quantification of the bed grain size distribution (GSD) of river surfaces is primarily conducted through manual approaches in the field. These methods are time consuming and not able to accurately represent the spatial diversity of the grain size distribution of rivers. Recently, several software programs and procedures have been developed using semi-automatic and automatic methods to estimate bed GSD from digital imagery. The purpose of this study is to compare softwares accuracy between reference GSDs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In the past years, applications of semi-automatic grain size measuring methods, where algorithms model ellipsoids around single grains, have gained an increasing popularity (Detert and Weitbrecht, 2012;Purinton and Bookhagen, 2019). Despite improvements in such techniques, measuring sizes of fluvial gravels in an accurate and reproducible way still bears challenges (e.g., Chardon et al, 2021;Purinton and Bookhagen, 2021;Mair et al, 2022).…”
Section: Measuring Grains From Gravelly Riverbedsmentioning
confidence: 99%
“…In the past years, applications of semi-automatic grain size measuring methods, where algorithms model ellipsoids around single grains, have gained an increasing popularity (Detert and Weitbrecht, 2012;Purinton and Bookhagen, 2019). Despite improvements in such techniques, measuring sizes of fluvial gravels in an accurate and reproducible way still bears challenges (e.g., Chardon et al, 2021;Purinton and Bookhagen, 2021;Mair et al, 2022).…”
Section: Measuring Grains From Gravelly Riverbedsmentioning
confidence: 99%
“…We base this inference on the results of other analyses, which were accomplished with the same segmentation software and which documented a systematic underestimation of related percentile values, thus hinting at an effect related to over-segmentation (Chardon et al, 2022). This issue might be addressed if (i) images are segmented semi-automatically where manual measurements are accomplished occasionally to set a benchmark (Purinton and Bookhagen, 2021), (ii) reference measurements are conducted for calibration purposes (Chardon et al, 2022), or if (iii) the automated segmentation is improved. However, more research is needed to improve our understanding of systematic traits of segmentation-based grain sizes and the related dependency on survey-specific characteristics.…”
Section: Grain Size Accuracy Compared To Field Measurementsmentioning
confidence: 93%
“…Second, other segmentation-based approaches, e.g., Basegrain (Detert and Weitbrecht, 2012) or manual segmentation (Sulaiman et al, 2014), require manual processing of each image and are therefore not suitable for the large number of processed images as is the case in this study. We acknowledge that there are known shortcomings of Pebble-Counts, and we refer to Chardon et al (2022) for a comparison with other software results and to Purinton and Bookhagen (2021) for mitigation strategies of some shortcomings.…”
Section: Grain Size Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, semiautomated or fully automated particle size calculation software based on digital images has been developed. 22 Schmitt et al 23 compared various grain size estimation software and found that all of them underestimated the actual grain size. In addition, the cobbles often cover each other on the bed surface, resulting in incomplete edges after image segmentation.…”
Section: Introductionmentioning
confidence: 99%